Obstetric outcomes and antenatal access among adolescent pregnancies in KwaZulu-Natal, South Africa. Issue 1 (23rd January 2018) - Govender, T; Reddy, P; Ghuman, S
Abstract : Background: Pregnancy among adolescents in South Africa is a growing concern as it may be associated with adverse socio-economic and health impacts. Timeous initiation and optimal utilisation of antenatal care (ANC) services is imperative to ensure positive pregnancy outcomes. However, this is not always possible owing to various challenges. Methods: A multi-method study design using both retrospective record review and qualitative interviews was undertaken at a district hospital on the North Coast of KwaZulu-Natal, South Africa. Data on ANC attendance trends and obstetric/perinatal outcomes for all recorded adolescent pregnancies (13–16 years) at the district hospital under study was collected over 3 years (2011–2013) ( n = 314). Qualitative interviews with randomly selected pregnant adolescents were conducted to assess experiences of ANC access and utilisation. Results: Late ANC booking and reduced ANC visits were common for adolescent pregnancies. Under-utilisation of ANC (i.e. less than 4 visits) was significantly associated with lower gestational age (< 37 weeks) (OR = 2.64; 95% CI = 1.04; 6.74; p < 0.05). Low birthweight, low Apgar scores as well as the incidence of maternal anaemia and pregnancy-induced hypertension (PIH) were found to be related to late ANC booking. In-depth interviews suggested that teenagers suffered emotional vulnerability linked to family, partner and financial support. They discussed various barriers linked with accessing ANC while acknowledging perceived benefits. Conclusion: Adolescent pregnancy was associated with late booking and reduced ANC visits, which was a risk for adverse maternal health outcomes. In-depth interviews suggested numerous challenges associated with ANC access including; financial barriers, attitude of healthcare workers (HCWs), long queues, distance travelled to access ANC services, human immunodeficiency virus (HIV) status and a lack of knowledge.